GAMBARAN PENGETAHUAN SISWA SEKOLAH MENENGAH ATAS TERHADAP PROTOKOL KESEHATAN DI SMAN 4 BANGKO PUSAKO - Oka Fatmanita; Bayhakki Bayhakki; Darwin Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Introduction: Health protocols are health procedures, rules, and standards that must be adhered to in order to anticipate the transmission of Covid-19. High school students should have high knowledge of health protocols to break the chain of spread of Covid-19. This study aims to describe the knowledge of high school students on health protocols. Methods: This study used a descriptive design with a sample of 86 respondents who were taken using a simple random sampling technique. The research instrument used was a questionnaire made by the researcher himself, the results obtained were r table (0.444) < r count (0.472-0.879 and crombach's negligence in this research questionnaire was 0.942. The data analysis used was univariate analysis. Results: The majority of respondents aged 17 years (33.7%) and the gender of the majority of women as many as 49 students (57%). The results of the study explained that 54 students (62.8%) had high knowledge of health protocols, high knowledge of 67 students (77.9%) wearing masks protocols, high knowledge 50 students (58.1%) of hand washing protocols, high knowledge of 68 students (79.1%) of social distancing protocols, high knowledge of 56 students (65.1%) of protocols avoiding crowds, high knowledge of 48 students (55.8%) of protocols reducing mobility. Conclusion: The majority of students have moderate knowledge of health protocols Suggestion: for further researchers to increase the number of samples in p research and examine the factors that influence the level of knowledge and behavior of students in implementing health protocols.Keywords: Knowledge, health protocol, high school students